2023
DOI: 10.1080/13880209.2023.2244543
|View full text |Cite
|
Sign up to set email alerts
|

Loke zupa decoction attenuates bronchial EMT-mediated airway remodelling in chronic asthma through the PI3K-Akt/HIF-1α signaling pathway

Jiani Liu,
Li Li,
Xue Han
et al.

Abstract: Context Loke zupa decoction (Lok) is a well-established classic Chinese folk remedy for asthma. Objective We sought to investigate the effect and mechanism of Lok on asthma airway remodelling and provide novel insights for the prevention and treatment of asthma. Materials and methods For in vitro experiments, BEAS-2B cells were assigned into six groups: Control, TGF-β1 (10 μM), TGF-β1 + Lok-20, TGF-β1 + Lok-40, TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The MAPK/Akt pathway is an important signaling pathway in asthma formation that participates in airway remodeling and inflammation (Liu et al 2023 ; Lyu et al 2022 ; Jin et al 2023 ). To further identify the possible involved signaling pathway, we determined the expression levels of MAPK and Akt, which are important components of the MAPK/Akt pathway (Ma et al 2016 ; Bai et al 2022 ; Liu et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK/Akt pathway is an important signaling pathway in asthma formation that participates in airway remodeling and inflammation (Liu et al 2023 ; Lyu et al 2022 ; Jin et al 2023 ). To further identify the possible involved signaling pathway, we determined the expression levels of MAPK and Akt, which are important components of the MAPK/Akt pathway (Ma et al 2016 ; Bai et al 2022 ; Liu et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yadav et al reported that the inhibition of aldose reductase prevents TGF-β1-induced EMT in airway epithelial cells and airway remodeling in ovalbumin (OVA)-induced asthmatic model mice via inhibiting the TGF-β1/PI3K/AKT/GSK-3β signaling pathway [ 55 ]. Additionally, Liu et al reported that Lok, which is a traditional folk medicine widely used in northwest China for asthma, inhibits EMT in OVA-induced asthmatic model mice and TGF-β1-induced EMT in airway epithelial cells through inhibiting the PI3K/AKT/HIF-1α signaling pathway [ 56 ]. These results indicate that TGF-β1 activates the PI3K/AKT signaling pathway in a Smad-independent manner during EMT, which causes fibrosis in asthmatic airway remodeling.…”
Section: The Molecular Mechanism Of Emt In Fibrosis Of Asthmatic Airw...mentioning
confidence: 99%